Implementasi Pembelajaran Berdiferensiasi Dalam Peningkatan Minat Belajar Bahasa Arab Siswa Kelas 8 Studi Kasus Di SMPAl-Madina Wonosobo - Frans Maulana Andika; Noor Aziz; Chairani Astina (DAS Institute, 2024)
The background of this study is the teacher's teaching methods in the classroom are somewhat varied, and the lack of enthusiasm of students towards the subject matter makes them less involved in the learning process. This problem is very detrimental to the academic performance of students learning Arabic. This study was conducted for two months. Students of grade VIII of SMP Al-Madina Wobosobo were involved in the research process. This study uses a qualitative research design with a field research design type. Data collection techniques use documentation, interviews, and observations. The data analysis technique used by researchers is called qualitative data analysis, which consists of three stages: data collection, data reduction, data analysis, and drawing conclusions from data.The results of this study indicate that: 1) Differentiated learning can determine students themselves according to their needs and learning styles and make it easier for students to channel learning activities in class. The teacher's steps in implementing differentiated learning are by grouping students according to their learning needs and interests, providing learning media according to student needs and explaining the material that has been loaded in different forms. 2) Factors that can influence students' interest in learning Arabic are divided into two, namely internal factors and external factors. Internal factors come from students' enthusiasm or interest in learning Arabic and from teachers' motivation towards their students, while external factors come from learning media obtained in class. 3) The impact of differentiated learning implemented at SMP Al-Madina Wonosobo is divided into two, namely positive and negative impacts. The positive impact is an increase in students' motivation to learn Arabic, while the negative impact is in learning that requires a lot of time such as requiring two meetings for one material and there are limitations in learning.